Harmony of Paradox and Contradiction: Communication between Human Beings and God according to Hermann Cohen’s Jewish Philosophy - Alon-Altman, Talya (Journal of media and religion, 2020)
This article examines communication between a human being and God in the Jewish philosophy of the German-Jewish philosopher, Hermann Cohen (1842-1918). It observes Cohen’s Jewish philosophy in light of communication theories, using the theoretical wealth of a relatively new discipline - communication, in order to deepen the philosophical and theological discussion. This new perspective enriches our view of philosophy, theology, and offers a fresh and novel approach to the philosophical and theological study of communication, and media theology in particular.